The Skill-Specific Impact of Past and Projected Occupational Decline - Lena Hensvik; Oskar Nordström Skans (Institute of Labor Economics (IZA), 2020)
Using population-wide Swedish register data on cognitive abilities and productive personality traits, we show that employment growth has been monotonically skill-biased in terms of these general-purpose intellectual skills, despite a simultaneous (polarizing) decline in middle-wage jobs. Employees in declining mid-wage occupations have comparably little of these general intellectual skills. Conversely, growing low-wage occupations are more (intellectually) skill-intensive than other low-wage jobs. Employment has primarily increased in occupations where workers are endowed with verbal and technical abilities, and social maturity. Existing occupational projections imply that the relationship between employment growth and skills in the projected future will resemble the past.
Keywords: J21; J31; 330; skills; polarization; future of work